2015
DOI: 10.1016/j.toxrep.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric studies of the effects of Telfairia occidentalis on alcohol-induced gonado-toxicity in male rats

Abstract: BackgroundAvailable evidence suggests that 50% of couples with infertility are male related. Over 40% of these males consume alcohol which has been reported to be a reproductive toxicant causing depletions in the epithelium of seminiferous tubules hence reducing sperm counts and sperm morphology.ObjectiveTo determine the effects of aqueous leaf extract of Telfairia occidentalis on alcohol-induced cyto-architectural changes in the testis.MethodsAqueous leaf extract of Telfairia occidentalis (T. occidentalis) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…The dose dependent significant increase in sperm count alone and non significant increase in sperm motility and morphology observed in this study demonstrated the efficacy of T. occidentalis over a long period of time at a substantial dose. However, it negated studies by [ 18 ] whose reports showed a significant decrease (P < 0.05) in sperm count and morphology. Another reason for the increase in sperm count may be due to the reparative effect of the phytochemicals present in the TO.…”
Section: Discussioncontrasting
confidence: 68%
“…The dose dependent significant increase in sperm count alone and non significant increase in sperm motility and morphology observed in this study demonstrated the efficacy of T. occidentalis over a long period of time at a substantial dose. However, it negated studies by [ 18 ] whose reports showed a significant decrease (P < 0.05) in sperm count and morphology. Another reason for the increase in sperm count may be due to the reparative effect of the phytochemicals present in the TO.…”
Section: Discussioncontrasting
confidence: 68%
“…The consequence of prolonged toxic xenobiotics on actively dividing cells during spermatogenetic cell division ultimately resulting in cessation may also play a significant role in germinal cell degeneration (Vidal & Whitney, ). Our result agrees with previous studies which reported that the induction of HAART (Azu et al ., ; Ogedengbe et al ., ) or alcohol (Dosumu et al ., ; Akang et al ., ) causes severe effects on germinal cells leading to extensive necrosis and disruption of spermatogenensis. Decreased seminiferous tubular diameter, widened lumen, and hypocellular interstitium were also observed.…”
Section: Discussionmentioning
confidence: 99%
“…Morphometric studies were carried out as reported by Akang et al (2015). The primary aim was to estimate the volumes of seminiferous tubule epithelium (seminiferous epithelium) and interstitium in the testes.…”
Section: Methodsmentioning
confidence: 99%